The influence of athletic performance on the highest positions of the final ranking during 2017/2018 Serie A season - Longo, U. G.; Sofi, F.; Candela, V.; Risi Ambrogioni, L.; Pagliai, G.; Massaroni, C.; Schena, E.; Cimmino, M.; D`Ancona, F.; Denaro, V. (BMC Sports Science, Medicine and Rehabilitation, 2021)
Background: Our previous study on the 2016/2017 Serie A season showed that a greater likelihood of reaching the top positions in the Italian league "Serie A" seemed to be mainly related to sprint activity, goal attempts, total throws, target shots and assists. Therefore, we aim to evaluate the following season data in the same league to compare, confirm, and improve these results. Methods: The data of all the matches played during the "Serie A" 2017-2018 season were obtained from the Italian soccer league. The teams` analysis was performed in terms of total distance covered in km, jogging, running and sprint activities, average speed, and match statistics (total shots, shots on target, goal attempts, assists, turnovers, and steals). Results: Teams that reached the first four positions revealed a lower percentage of running (65.98 ± 1.51 vs. 66.84 ± 2.18; p < 0.001), a higher percentage of jogging (25.61 ± 1.71 vs. 25.30 ± 1.97; p = 0.037) and sprint activities (8.41 ± 1.04 vs. 7.86 ± 0.82; p < 0.001). Match statistics seem to be statistically different between the first four teams the other teams. The total goals are strongly associated both with the total score at the end of the championship (R = 0.906; p < 0.001) and with the position in the final ranking (R = 0.850; p < 0.001). Conclusions: Our results suggest that high-level teams have a lower running rate and a higher percentage of jogging and sprinting than other teams.